(3OhQ GdJMhdGJ GdGbJUGOjI GdYGdejI aj JZjjQ HfjI GdfXGe GdOhdjs (3eHGOQI GdMRGe hGdWQjb EfehPLGs - (3GdaGdM(B, (3SdWGf YHO GdcQjes ((3YeGfs (3OGQ hGFd ddfTQ hGdJhRjYs, 2022)
(3NdajI GdOQGSI hCgejJgG, GdEWGQ GdfXQj hGdOQGSGJ GdSGHbI, GdfXGe GdOhdj GdLOjO(B: (3bQGAI aj GdeYGjjQ hGdSeGJ, eGgjI GdfXGe GdOhdj GdLOjO, eaghe GdfXGe GdOhdj aj GdYdGbGJ GdOhdjI, echfGJ GdfXGe GdOhdj, HfjI GdfXGe GdOhdj hJhRjY Gdbhi, JMhdGJ GdfXGe GdOhdj GdLOjO heYGjjQ GdbhI, GdJMhdGJ GdJj WQCJ Ydi GdfXGe GdOhdj GdLOjO , eYGjjQ JUfja eQGcR Gdbhi GdOhdjI, JMhdGJ GdbhI ZOGI CMOGK (B11 (3SHJeHQ (B2001(3, GdUQGY GdCeQjcj GdUjfj(B: (3GdGSJQGJjLjGJ hGdJOGYjGJ, WHjYI GdUQGY GdCeQjcj(B- (3GdUjfj, JOGYjGJ GdUQGY GdCeQjcj(B- (3GdUjfj, GdJMhdGJ GdGbJUGOjI GdOhdjI deQMdI eGHYO GdMQH GdHGQOI, GdfXGe GdGbJUGOj GdOhdj(B: (3Gdeaghe GdSeGJ, GdSeGJ, GdJWhQ, eaghe GdfXGe GdGbJUGOj GdOhdj, eUGOQ GdfXGe GdGbJUGOj GdOhdj, JWhQ GdfXGe GdGbJUGOj GdOhdj, SeGJ GdfXGe GdGbJUGOj GdOhdj, GdCMGOjI GdbWHjI ddfXGe GdGbJUGOj GdOhdj fbGW GdVYa hGdbhI, YhGed GdbhI aj GdfXGe GdGbJUGOj GdOhdj aj Xd GdGMGOjI GdbWHjI, YhGed GdVYa aj GdfXGe GdGbJUGOj GdOhdj aj Xd GdGMGOjI GdbWHjI, GdJMhdGJ GdGbJUGOjI GdOhdjI GdLOjOI, GdJMhdGJ GdGbJUGOjI GdOhdjI eG HYO GdMQH GdHGQOI (B1990-2008(3, GdJMhdGJ GdGbJUGOjI GdOhdjI eGHYO GdCReI GdeGdjI (B2008-2020(3, eHGOQI GdMRGe hGdWQjb heSJbHd GdfXGe GdOhdj GdLOjO, eGgjI eHGOQI GdMRGe hGdWQjb(B: (3GdJYQja, GdGSJQGJjLjI, GdCgOGa, GdCHYGO, GdJYQja hGdJCUjd GdJGQjNj dWQjb GdMQjQ, eHGOQI GdMRGe hGdWQjb(B: (3GdQDjI GdGSJQGJjLjI, CgOGa hCHYGO eHGOQI GdMRGe hGdWQjb, JMOjGJ eHGOQI GdMRGe hGdWQjb, JMOjGJ OhdjI, JMOjGJ chfjI (B((3LGFMI chQhfG(B)(3, ecGfI GdUjf heSJbHd GdfXGe GdOhdj GdLOjO, ecGfI GdUjf GdOhdjI, eSJbHd GdfXGe GdOhdj GdLOjO(B.s
Keywords: (3GdGbJUGO GdOhdjs